A versatile nanoreactor for complementary in situ X‐ray and electron microscopy studies in catalysis and materials science. (27th August 2019) - Fam, Yakub; Sheppard, Thomas L.; Becher, Johannes; Scherhaufer, Dennis; Lambach, Heinz; Kulkarni, Satishkumar; Keller, Thomas F.; Wittstock, Arne; Wittwer, Felix; Seyrich, Martin; Brueckner, Dennis; Kahnt, Maik; et al.
Abstract : A series of nanoreactors have been developed for complementary in situ X‐ray and electron microscopy. The setup was utilized to monitor thermal annealing processes of porous materials under controlled atmospheres with hard X‐ray ptychography. Abstract : Two in situ `nanoreactors' for high‐resolution imaging of catalysts have been designed and applied at the hard X‐ray nanoprobe endstation at beamline P06 of the PETRA III synchrotron radiation source. The reactors house samples supported on commercial MEMS chips, and were applied for complementary hard X‐ray ptychography (23 nm spatial resolution) and transmission electron microscopy, with additional X‐ray fluorescence measurements. The reactors allow pressures of 100 kPa and temperatures of up to 1573 K, offering a wide range of conditions relevant for catalysis. Ptychographic tomography was demonstrated at limited tilting angles of at least ±35° within the reactors and ±65° on the naked sample holders. Two case studies were selected to demonstrate the functionality of the reactors: (i) annealing of hierarchical nanoporous gold up to 923 K under inert He environment and (ii) acquisition of a ptychographic projection series at ±35° of a hierarchically structured macroporous zeolite sample under ambient conditions. The reactors are shown to be a flexible and modular platform for in situ studies in catalysis and materials science which may be adapted for a range of sample and experiment types, opening new characterization pathways in correlative multimodal in situ analysis of functional materials at work. The cells will presently be made available for all interested users of beamline P06 at PETRA III.